Cybersecurity essentials - Brooks, Charles J.; Grow, Christopher; Craig, Philip; Short, Donald (Sybex a Wiley brand, 2018)
"Provides an overview of the essential topics required for entry-level cybersecurity certifications, discussing the concepts and practices within securing the infrastructure, devices, local networks and the perimeter."--Provided by publisher.
Includes index. - Online resource; title from title page (Safari, viewed November 18, 2019)
Keywords: Computer networks -- Security measures; Computer security; datasikkerhet; datasikring; datanettverk; sikkerhet; lokale datanettverk; Réseaux d'ordinateurs; Sécurité; Mesures; Sécurité informatique; Computer networks; Security measures